2017
DOI: 10.1186/s12883-017-0950-y
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol improves endothelial function in acute cerebral ischemia patients: a double-blind placebo controlled trial with flow-mediated dilation technique

Abstract: BackgroundIn order to evaluate the impact of cilostazol on endothelial function, we compared the changes of flow-mediated dilation (FMD) between aspirin and cilostazol groups in patients with acute cerebral ischemia.MethodsPatients presenting with acute cerebral ischemic events were randomly assigned into aspirin (n = 40) or cilostazol (n = 40) group in a double-blinded manner. FMD was measured at baseline (T0) and 90 days (T1). We measured L-arginine at baseline (a precursor of biologically active nitric oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The time to randomization after diagnosis was <2 weeks in 8 (n=1940), 12 , 14 , 15 , 19 21 , 23 , 24 between 2 weeks and 6 months in 5 (n=2123), 13 , 18 , 25 27 and 6 months or later in 6 trials (n=6406; including the one trial in cognitive decline/dementia) 10 , 11 , 16 , 17 , 22 , 28 and was not stated in the other trial in cognitive decline. 9 The duration of trial treatment was 4 weeks in 3 (n=344), 19 , 20 , 28 10 weeks in 1 (n=57), 11 4 months in 4 (n=1236), 12 , 20 , 22 , 23 6 to 8 months in 5 (n=753; including both trials in cognitive decline/dementia), 9 , 10 , 14 , 15 , 18 12 months in 1 (n=68), 27 and between 12 months and 5 years in 6 trials (n=8034).…”
Section: Resultsmentioning
confidence: 99%
“…The time to randomization after diagnosis was <2 weeks in 8 (n=1940), 12 , 14 , 15 , 19 21 , 23 , 24 between 2 weeks and 6 months in 5 (n=2123), 13 , 18 , 25 27 and 6 months or later in 6 trials (n=6406; including the one trial in cognitive decline/dementia) 10 , 11 , 16 , 17 , 22 , 28 and was not stated in the other trial in cognitive decline. 9 The duration of trial treatment was 4 weeks in 3 (n=344), 19 , 20 , 28 10 weeks in 1 (n=57), 11 4 months in 4 (n=1236), 12 , 20 , 22 , 23 6 to 8 months in 5 (n=753; including both trials in cognitive decline/dementia), 9 , 10 , 14 , 15 , 18 12 months in 1 (n=68), 27 and between 12 months and 5 years in 6 trials (n=8034).…”
Section: Resultsmentioning
confidence: 99%
“…We included 18 randomised trials comprising 11 429 patients in the ITT population [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (tables 1 and 2). Nine studies were conducted in Japan, four in Korea, two in China, two in multiple East Asian countries and one in the UK.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Cilostazol is widely used in patients with coronary artery disease after receiving PCI to reduce the risk of thrombotic events. The beneficial effects of cilostazol appear to extend beyond its obvious antiplatelet effects, and have been attributed to its reduction of in-stent and in-segment restenosis [28][29][30], protective effect against ischemia-reperfusion injury [31] and improvement of endothelial function [32,33]. A recent research suggested that cilostazol could inhibit apoptosis in some circumstances to protect cell viability [34] indicating that cilostazol might protect endothelia in a similar way.…”
Section: Discussionmentioning
confidence: 99%